The Study of Vibration Characteristics in Head Stock of a lathe Machine at Different Cutting Conditions - Kasab, Safeen Y.; Baban, Sherko A. (Sulaimani Journal for Pure and Applied Sciences, 2007)
This paper presents a study of vibration characteristics in headstock of a lathe machine, at different cutting parameters. These parameters are the cutting speed; the depth of cut lnq the feed rate .The transducer were used on the heidstock in two directions, the vertical and horizontal (feed) direction, Also for a time domain of (l0sec) in both directions. The results show that the effect of the vertical vibrations is more significanf than the horizontal (feed) direction, for all of the cases investigated in this paper. Unlike the veriical vibration, the horizontal vibration is lower and steadier, when the cutting speed, ine Oepttr of cut and the feed rate are increased, Whereas the vertical vibration shows a great fluctuation when these parameters are increased.
Keywords: Vibration characteristics; cutting parameters; head stock